Challenges and opportunities for health policy and systems research funding in the Western Pacific region - Swee Kheng Khor (Public Health Research & Practice, 2021)
Objectives and importance of study: This study examines how health policy and systems research (HPSR) is funded in eight countries and areas in the World Health Organization Western Pacific Region (WPRO). The aim of the research is to provide a guide for HPSR practitioners and organisations to understand the landscape of research funding priorities across the WPRO and to inform demand generation and advocacy activities for HPSR funding and output. Study type: Mixed methods. Methods: A desk review was conducted relating to HPSR funding, followed by in-depth interviews. Eight countries and areas were selected to represent characteristics of different health systems. Literature reviews included an analysis of available data relating to HPSR funding and national research and development (R&D) budgets, between 2010 and 2019 (inclusive). In-depth interviews were conducted with 23 stakeholders using an approved interview guide, to assess the attitudes of HPSR funding decision makers towards HPSR, determinants for HPSR and health research funding decisions, and proposals to strengthen HPSR funding and output. Results: There are four main characteristics of HPSR funding in the WPRO: 1) a general absence of studies on HPSR funding and its determinants; 2) no universally accepted understanding of HPSR; 3) an absence of granular health research funding data in general and for HPSR in particular; and 4) HPSR funding is generally perceived to be minimal. In-depth interviews show that HPSR has different interpretations and emphases across WPRO countries, leading to a fragmented landscape where decision makers generally favour biomedical or clinical research. Participants indicate that political involvement increases overall research funding, especially if there is a clear connection between funders, producers and HPSR users. Suggestions from participants to strengthen HPSR include: appropriately using central agencies to generate demand and raise HPSR as a national priority; adopting interdisciplinary HPSR; and building HPSR capacity and organisational structures. Conclusions: HPSR in the Western Pacific region is generally not well funded, with biomedical and public health research often perceived as a higher priority. Although funding is a crucial component of the quality, quantity and relevance of HPSR outputs, HPSR practitioners and organisations must also generate demand for HPSR, build capacity for increasing the quantity and quality of HPSR outputs, and build pathways to translate HPSR outputs into real-world policies.